Multimodal cantilevers with novel piezoelectric layer topology for sensitivity enhancement - Moore, Steven Ian; Ruppert, Michael G.; Yong, Yuen Kuan (Beilstein Journal of Nanotechnology, 2017)
Self-sensing techniques for atomic force microscope (AFM) cantilevers have several advantageous characteristics compared to the optical beam deflection method. The possibility of down scaling, parallelization of cantilever arrays and the absence of optical interference associated imaging artifacts have led to an increased research interest in these methods. However, for multifrequency AFM, the optimization of the transducer layout on the cantilever for higher order modes has not been addressed. To fully utilize an integrated piezoelectric transducer, this work alters the layout of the piezoelectric layer to maximize both the deflection of the cantilever and measured piezoelectric charge response for a given mode with respect to the spatial distribution of the strain. On a prototype cantilever design, significant increases in actuator and sensor sensitivities were achieved for the first four modes without any substantial increase in sensor noise. The transduction mechanism is specifically targeted at multifrequency AFM and has the potential to provide higher resolution imaging on higher order modes.
Keywords: atomic force microscopy; multifrequency AFM; multimodal AFM; piezoelectric cantilever, self-sensing